Peran Bank Syariah Dalam Kebijakan Moneter untuk Stabilitas Ekonomi di Indonesia - Fitri Rohimah; Nurul Farhah; Arini Jannati; Rasidah Novita Sari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This article analyzes the role of Islamic banks in supporting monetary policy in Indonesia and its impact on national economic stability. Using library research methods, this research examines relevant literature regarding the development of the sharia banking sector and sharia-based monetary instruments. The research results show that Islamic banks make a significant contribution to stabilizing inflation, increasing financial access, and managing liquidity through instruments such as the Bank Indonesia Sharia Certificate (SBIS) and the sharia interbank money market. In addition, Islamic banks play a role in providing financing for micro, small and medium enterprises (MSMEs), which is important for inclusive economic growth. Nevertheless, challenges such as low sharia financial literacy and limited policy instruments need to be overcome to maximize the contribution of sharia banks to monetary policy. This research is expected to provide in-depth insight into the potential and challenges faced by Islamic banks in supporting the stability of the Indonesian economy.